2015
DOI: 10.1007/s12576-015-0419-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-genomic regulation and disruption of spermatozoal in vitro hyperactivation by oviductal hormones

Abstract: During capacitation, motility of mammalian spermatozoon is changed from a state of "activation" to "hyperactivation." Recently, it has been suggested that some hormones present in the oviduct are involved in the regulation of this hyperactivation in vitro. Progesterone, melatonin, and serotonin enhance hyperactivation through specific membrane receptors, and 17β-estradiol suppresses this enhancement by progesterone and melatonin via a membrane estrogen receptor. Moreover, γ-aminobutyric acid suppresses progest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 65 publications
1
46
0
Order By: Relevance
“…In mouse and hamster epididymal spermatozoa, hyperactivation can be induced highly in vitro by incubation in a capacitation‐supporting medium, including HCO 3 − , Ca 2+ , and cholesterol acceptors . Researches with hamster epididymal spermatozoa proposed that occurrence of hyperactivation is hastened or delayed by the interaction with specific fluid components of female reproductive tracts, such as progesterone, 17β‐estradiol, melatonin, serotonin and γ‐aminobutyric acid, probably in order to modulate the timing of arrival of capacitated/acrosome‐reacted spermatozoa at the oviductal ampulla where ovulated oocytes are ready for the fertilization . In bull and boar ejaculated spermatozoa, by contrast, it may be difficult to induce hyperactivation highly by the simple incubation in the capacitation‐supporting medium .…”
Section: Roles and Characteristics Of Flagellar Hyperactivationmentioning
confidence: 99%
See 1 more Smart Citation
“…In mouse and hamster epididymal spermatozoa, hyperactivation can be induced highly in vitro by incubation in a capacitation‐supporting medium, including HCO 3 − , Ca 2+ , and cholesterol acceptors . Researches with hamster epididymal spermatozoa proposed that occurrence of hyperactivation is hastened or delayed by the interaction with specific fluid components of female reproductive tracts, such as progesterone, 17β‐estradiol, melatonin, serotonin and γ‐aminobutyric acid, probably in order to modulate the timing of arrival of capacitated/acrosome‐reacted spermatozoa at the oviductal ampulla where ovulated oocytes are ready for the fertilization . In bull and boar ejaculated spermatozoa, by contrast, it may be difficult to induce hyperactivation highly by the simple incubation in the capacitation‐supporting medium .…”
Section: Roles and Characteristics Of Flagellar Hyperactivationmentioning
confidence: 99%
“…[38][39][40][41] Researches with hamster epididymal spermatozoa proposed that occurrence of hyperactivation is hastened or delayed by the interaction with specific fluid components of female reproductive tracts, such as progesterone, 17β-estradiol, melatonin, serotonin and γaminobutyric acid, probably in order to modulate the timing of arrival of capacitated/acrosome-reacted spermatozoa at the oviductal ampulla where ovulated oocytes are ready for the fertilization. 42,43 In bull and boar ejaculated spermatozoa, by contrast, it may be difficult to induce hyperactivation highly by the simple incubation in the capacitation-supporting medium. [44][45][46][47] This suggests existence of strong suppressors (eg a calyculin-sensitive protein phosphatase) for hyperactivation in the spermatozoa from livestock.…”
Section: Induction Of Hyperactivation In Vitromentioning
confidence: 99%
“…PEBP1 has been identified among potential 'decapacitation factors' that were able, when added in vitro to suspensions of mouse spermatozoa, to inhibit sperm ability to undergo P 4 -induced acrosome reaction and to bind to the zona pellucida (Gibbons et al 2005, Nixon et al 2006. Thus, the increase in P 4 in the oviduct at the time of ovulation, in addition to triggering sperm hyperactivation (Fujinoki et al 2016), may allow the inhibition of such decapacitation factor and finally contribute to the presence of spermatozoa able to fertilize around the oocyte.…”
Section: Figurementioning
confidence: 99%
“…It is possible that Maca induces the acrosome reaction and hyperactivation because of an increase in cAMP and the number of spermatozoa with high MMP. Furthermore, it has recently been suggested that some hormones, including progesterone, melatonin, and serotonin, enhance hyperactivation through specific membrane receptors and that 17β‐estradiol suppresses such enhancement by progesterone and melatonin via a membrane estrogen receptor . Because plant extracts can have several functions, including estrogenic actions, depending on the flavonoids present, it is possible that Maca also has a specific estrogenic action.…”
Section: Discussionmentioning
confidence: 99%